The Role of Socioeconomic Determinants on Individual Decision to Quit Smoking: Evidence from Indonesia. - Muhammad, Rizkan; Nursani (Universitas Airlangga, 2023)
The Global Adult Tobacco Survey in 2020 shows that Indonesia became the world's third-highest number of smokers. This is due to the excessive consumption of cigarettes by the Indonesian people and the lack of awareness of the effects of smoking. This study aims to investigate the socioeconomics as an indicator that has a high probability of being a determinant of individual decisions in households to quit smoking and uses the latest Indonesia Family Life Survey (IFLS-5). The Probit approach was used to analyze the most identified factors for preventive ways and propose interventions to address those factors. We find some facts, namely (1) The higher the level of education and income of the individual in the household, the higher the probability of the individual's decision to quit smoking; (2) unlike cigarette expenditure, the more significant the increase in cigarette expenditure, the lower the individual's probability of quitting smoking; (3) but, unfortunately, the existence of a non-smoking area does not influence individuals in the household to quit smoking, this also applies to individual smokers who are sick. We also found that several control variables, such as (4) increasing age and marital status (married), had a positive effect on an individual's decision to quit smoking; (5) individuals who were male had a lower probability of quitting smoking than females. In addition, (6) both individuals with marital status (divorced) and occupation do not affect the decision to quit smoking.